2018
DOI: 10.18677/agrarian_academy_2018b7
|View full text |Cite
|
Sign up to set email alerts
|

EFEITO CITOTÓXICO E GENOTÓXICO DE Crescentia cujete L. (BIGNOCIACEAE) ATRAVÉS DO BIOTESTE Allium cepa

Abstract: RESUMO Crescentia cujete L. (Bignoniaceae), conhecida popularmente como coité, é uma árvore que pode chegar até 10 metros de altura, bastante utilizada na medicina popular para tratar diarreia, dores de estômago, bronquite, tosse, asma, uretrite, dores de cabeça, hipertensão e diurética. O objetivo deste estudo foi avaliar o efeito citotóxico e genotóxico desta espécie sob o bioteste Allium cepa sob diferentes concentrações de infusão. Foi utilizada 0,45; 0,90 e 1,35 gramas/L de folhas de Crescentia cujete L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(7 reference statements)
0
2
0
1
Order By: Relevance
“…In previous studies, some bioactive compounds of Crescentia cujete have already been isolated and identified through spectrometric techniques, such as preliminary phytochemical and chromatographic screenings. It is reported by Macedo et al (2018) that several compounds are present in the leaf extract, the main ones being naphthoquinones, glycosides, plumeride, aucubin, irioids and asperuloside.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, some bioactive compounds of Crescentia cujete have already been isolated and identified through spectrometric techniques, such as preliminary phytochemical and chromatographic screenings. It is reported by Macedo et al (2018) that several compounds are present in the leaf extract, the main ones being naphthoquinones, glycosides, plumeride, aucubin, irioids and asperuloside.…”
Section: Resultsmentioning
confidence: 99%
“…Then the Kif2a protein tries to repair the damage, if it is not possible to reverse the situation then the anomalies arise, and the cell blocks the division process mainly in the anaphase, causing irregularities such as lagging and chromosomal breaks (Macedo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, a fase orgânica da C. Cujete L., inibiu 100% a germinação das sementes das duas espécies receptoras, obtendo o efeito citotóxico na concentração de 0,5%, considerada relativamente baixa (PEREIRA MS, et al, 2015). Macedo WA, et al (2018) concluíram em estudo que a espécie pode ser tóxica ao organismo humano e animal, em seus ensaios pode observar que houve presença de anomalias e baixo índice mitótico ocasionando baixa divisão celular em concentrações mais elevadas.…”
Section: Atividades Biológicas Embasadas Cientificamenteunclassified